Northern triangle and Mexican news media perspectives on the migration crisis: strategic narrative and the identification of good action. (2nd September 2022) - Cooley, Skye; Hinck, Robert; Sample, Ethan
ABSTRACT: The goal of this study was to determine Northern Triangle (NT) migrants' motivations for traveling to the US by examining regional media narratives describing how these political communities make sense of migration's causes, solutions, and payoffs. Understanding these motivations is pivotal for crafting effective policy, especially given that mass migration from NT countries to the US continues to rise, with increasing numbers of families and unaccompanied children risking the journey despite higher levels of family unit apprehensions by CBP. The specific research questions this study answer concern first, how NT and Mexican media narratives on migration confront violence, institutional failures of state systems, and discuss incentives for migration (See Tables 2–4 for descriptive breakdown). Second, the study examines the larger context of how migration is made sense of in NT and Mexican media, including how US policy is viewed, through analysis of its discussions of migration routes, characterizations of migrants, the consequences of migration for the NT, Mexico, and the US, and identifies moral depictions of what good action may be in the form of policy. This research was funded by the Department of Homeland Security through the Center for Accelerating Operational Efficiency at Arizona State University: G10002513.